Small Bowel Injury During Laparoendoscopic Single-Site Surgery for Simple Nephrectomy - Joshi, Shreyas S. (Society of Laparoendoscopic Surgeons, 2013)
BACKGROUND AND OBJECTIVES: A 71-year-old man underwent a right simple nephrectomy via the laparoendoscopic single-site surgery (LESS) approach for intractable right flank pain and gross hematuria. A postoperative diagnosis of duodenal injury was suspected by physical findings and confirmed by computed tomography imaging. METHODS: Emergency exploratory laparotomy revealed a <5-mm full-thickness perforation of the duodenum and an accompanying 1-cm seromuscular injury. RESULTS: The subsequent postoperative course was unremarkable except for a right intraabdominal seroma that resolved without intervention. CONCLUSION: LESS nephrectomy is an effective surgical approach, but more data are needed regarding its surgical outcomes and complications. This case shows that the LESS approach is not without the risk of life-threatening complications, and it must be performed by experienced surgeons in select patients who are notably interested in improved cosmesis, after an informed consent that includes the potential for complications.